The Nature of the Reinforcer in the Enhancement of Social Self-Esteem - Marshall, W.. L.; Christie, M. M.; Lanthier, R. D.; Cruchley, J. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper describes two controlled single-case studies and one group study investigating the enhancement of social self-esteem. The two singlecase analyses suggested the value of a self-managed reinforcement procedure that targetted positive self-evaluations, in enhancing the very low social confidence of two young women who presented at our clinic. The group study included 18 undergraduate volunteers (10 females and 8 males) who were markedly low in social self-esteem. This study compared the relative effectiveness of three self-management procedures: one where the emission of personalized positive self-evaluations was followed by a pleasant event; one where the pleasant event preceded the emission of the positive statements; and one where the positive statements were unrelated to any particular events. The latter procedure was significantly less effective than the former two, which were equally effective. Thus a self-managed procedure was demonstrated to be effective in enhancing social self-esteem but the underlying mechanisms of change were obscure.